Prevalence of thyroid disorders in pregnancy among women attending a tertiary hospital of Sudurpaschim province, Nepal - Bhatta, Surendra Prasad; Mishra, Pratibha; Chaudhary, Shiv Kumar (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Thyroid disorders are the second most common endocrine disorders affecting women in the reproductive period. Women with thyroid disorders during pregnancy are prone to serious maternal and fetal outcomes. To prevent those adverse outcomes, universal screening for thyroid disorders is recommended in the first trimester of pregnancy. This study aims to determine the prevalence of thyroid disorders during pregnancy in women attending a tertiary care hospital. Method: A descriptive cross-sectional study was done at Dadeldhura Hospital, Dadeldhura, after obtaining ethical approval from the Nepal Health Research Council. Pregnant women aged 18 years or older were enrolled in the study using convenience sampling, irrespective of gestational age, parity, gravida, and prepregnant thyroid status. Participants’ thyroid function tests were analyzed to assess their thyroid status. The prevalence of thyroid disorders was estimated, and descriptive statistical analysis of collected data was done using SPSS (Statistical Package for Social Services) version 20.0. Result: A total of 356 pregnant women were enrolled in this study. The prevalence of thyroid disorders was found to be 30%, with subclinical hypothyroidism being the most common disorder, observed in 60 (16.85%) women. This was followed by overt hypothyroidism in 22 (6.1%) women and subclinical hyperthyroidism in 21 (5.89%) women. Conclusion: The study identifies a high prevalence of thyroid disorders in pregnancy. Further studies with a larger number of pregnant women and at multiple centers are needed to validate the prevalence of thyroid disorders in pregnancy in Sudurpaschim Province.